1998
DOI: 10.1111/j.2042-7158.1998.tb06882.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Interaction between Fluoxetine and Imipramine as a Function of Elevated Serum Alpha-1-acid Glycoprotein Levels

Abstract: The effect of elevated serum alpha-1-acid glycoprotein (AAG) levels on the pharmacokinetic interaction between imipramine and fluoxetine has been examined by utilizing a novel strain of transgenic mice which express serum AAG levels several times greater than normal. Before fluoxetine treatment, serum imipramine levels were approximately three times greater in transgenic mice than in control mice. Despite higher serum imipramine levels in transgenic mice, brain drug levels were lower than those found in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is also of interest that in depressed patients there is a significant increase in the plasma protein alpha 1-acid glycoprotein (AAG) (Nemeroff et al, 1990), one of the major binding sites for Flx in plasma (the other one is serum albumin). Such an increase in AAG leads to a rise in total Flx concentration in plasma, but decreases the unbound fraction leading to a decrease in Flx and NFlx concentrations in the brain (Holladay et al, 1998).…”
Section: Discussion Low Levels Of Flx and Rbx Induce Specific Changesmentioning
confidence: 99%
“…It is also of interest that in depressed patients there is a significant increase in the plasma protein alpha 1-acid glycoprotein (AAG) (Nemeroff et al, 1990), one of the major binding sites for Flx in plasma (the other one is serum albumin). Such an increase in AAG leads to a rise in total Flx concentration in plasma, but decreases the unbound fraction leading to a decrease in Flx and NFlx concentrations in the brain (Holladay et al, 1998).…”
Section: Discussion Low Levels Of Flx and Rbx Induce Specific Changesmentioning
confidence: 99%
“…With regard to FLU as an inhibitor of CYP, kinetic studies have demonstrated that plasma and brain levels and pharmacological efficacy of both FLU and TCAs can be increased by their simultaneous administration [66][67][68]. This interaction can be explained by the fact that FLU is both a strong inhibitor of CYP2D6 [69] and a substrate of this isozyme.…”
Section: The Role Of Cytochrome P450mentioning
confidence: 95%